Endothelial Glucocorticoid Receptor Suppresses Atherogenesis—Brief Report. Issue 4 (April 2015) - Goodwin, Julie E.; Zhang, Xinbo; Rotllan, Noemi; Feng, Yan; Zhou, Han; Fernández-Hernando, Carlos; Yu, Jun; Sessa, William C.
Abstract : Objective—: The purpose of this study was to determine the role of the endothelial glucocorticoid receptor in the pathogenesis of atherosclerosis. Approach and Results—: Control mice and mice lacking the endothelial glucocorticoid receptor were bred onto an Apoe knockout background and subjected to high-fat diet feeding for 12 weeks. Assessment of body weight and total cholesterol and triglycerides before and after the diet revealed no differences between the 2 groups of mice. However, mice lacking the endothelial glucocorticoid receptor developed more severe atherosclerotic lesions in the aorta, brachiocephalic artery, and aortic sinus, as well as a heightened inflammatory milieu as evidenced by increased macrophage recruitment in the lesions. Conclusions—: These data suggest that the endothelial glucocorticoid receptor is important for tonic inhibition of inflammation and limitation of atherosclerosis progression in this model. Abstract : Supplemental Digital Content is available in the text.